2007
DOI: 10.1111/j.1464-410x.2007.06867.x
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐operative complications of holmium laser enucleation of the prostate: experience in the first 280 patients, and a review of literature

Abstract: OBJECTIVE To evaluate, in a prospective study, the complications in 280 patients undergoing holmium laser enucleation of the prostate (HoLEP) at our institution, and to review previous reports to determine the overall incidence and types of various complications, and analyse their causes and means of prevention. PATIENTS AND METHODS We analysed the patients’ demographic, peri‐operative and follow‐up data, and the complications during and after surgery. RESULTS HoLEP was completed successfully in 268 patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
152
3
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(178 citation statements)
references
References 39 publications
16
152
3
7
Order By: Relevance
“…2,15 In the present study, apex tissue was enucleated using the HoLEP technique. 16 A significant amount of lateral lobe tissue was found near the prostatic capsule, particularly in patients with larger prostates.…”
Section: Discussionmentioning
confidence: 99%
“…2,15 In the present study, apex tissue was enucleated using the HoLEP technique. 16 A significant amount of lateral lobe tissue was found near the prostatic capsule, particularly in patients with larger prostates.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have reported that there is little variation in operative efficiency between surgeons and that comparable times can be achieved 17,24 . We found that although there is a twenty minute increase in enucleation time associated with less experienced surgeons, there is minimal difference in morcellation time.…”
Section: Discussionmentioning
confidence: 99%
“…Dual irrigation is used to keep the bladder full and to improve visualization. Irrigation was placed approximately [24][25][26][27][28][29][30] inches above the level of the bladder. Unusually tough prostatic tissue (termed "beach balls") may occasionally be encountered during enucleation which can prolong morcellation time.…”
Section: Description Of Proceduresmentioning
confidence: 99%
“…In some cases, there may be urine extravasations or massive bleeding due to severe perforation from bladder injury requiring open surgery 17,18) . However, the possibility of bladder injury during morcellation is less than 10% and many research reports that the extent of bladder injury was not severe 19) . This study was comparable with previous studies in preventing and reducing the extent of bladder injury.…”
Section: Discussionmentioning
confidence: 99%